STRATEGI MEMBANGUN KARAKTER ANAK SEKOLAH DASAR PADA MASA PANDEMI COVID-19 - Eko Suhendro (Magistra)
Indonesia as a nation that respects tradition, which is widely known as a polite nation, respects differences and customs, existing culture. The Covid-19 pandemic that has hit almost the entire world for some time, including Indonesia, has greatly affected the character of students. pay attention to all parties that the character crisis and the declining morale of children due to this pandemic must be resolved immediately. The purpose of this study is to provide a conceptual view for teachers to maintain the intensity of learning with character content that can still be done even in emergency situations by implementing character building strategies. This research is a qualitative descriptive study used to obtain information related to effective strategies to build the character of elementary school students. The respondents of this study were teachers who opened 15 elementary school levels. Data collection techniques in the form of interviews. The results show that some of the implementation of character strategies carried out by development teachers after the Covid-19 pandemic is by labeling, being listeners, paying attention gently, not comparing, giving examples, involving children in activities, using gadgets, making joint rules, encouraging independent attitudes. . The hope of this research can be material for study and literacy for teachers who have difficulty in building character after the Covid-19 pandemic.